1998
DOI: 10.1128/mcb.18.11.6325
|View full text |Cite
|
Sign up to set email alerts
|

RhoA-Binding Kinase α Translocation Is Facilitated by the Collapse of the Vimentin Intermediate Filament Network

Abstract: The regulation of morphological changes in eukaryotic cells is a complex process involving major components of the cytoskeleton including actin microfilaments, microtubules, and intermediate filaments (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 73 publications
8
101
0
4
Order By: Relevance
“…34, No. 6, 2001 Taken together, our results and other accumulating data 14,15,36,37,41,42 raise the question about association of IF with signaling proteins as an important regulator of cell signaling. In this respect, the connection between 14-3-3 and IFs could act as an integrator between structure and signaling.…”
Section: Discussionsupporting
confidence: 57%
“…34, No. 6, 2001 Taken together, our results and other accumulating data 14,15,36,37,41,42 raise the question about association of IF with signaling proteins as an important regulator of cell signaling. In this respect, the connection between 14-3-3 and IFs could act as an integrator between structure and signaling.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have shown that Rho-kinase is distributed in the cytoplasm (Matsui et al, 1996) but is localized specifi cally at the cleavage furrow during cytokinesis (Kosako et al, 1999) and along actin stress fi bers (Kawabata et al, 2004) and vimentin intermediate fi laments (Sin et al, 1998). EGFP-Rho-kinase, coexpressed with MLC-RFP, distributed diffusely in the cytoplasm and was not found with MLC-RFP at the base of cells within the intact monolayer (Fig.…”
Section: Rho-kinase Accumulates At the Apical-lateral Border Of Cellsmentioning
confidence: 87%
“…The two ROCK isoforms are highly homologous, apart from their PH domains, and act on the same cellular substrates (Yoneda et al 2005(Yoneda et al , 2007. ROCKII recruitment to the membrane is GTP-RhoA dependent (Sin et al 1998) and the PH domain of ROCKII bound PtdIns(3,4,5)P 3 (Yoneda et al 2005). Therefore, membrane recruitment of ROCKII downstream from Rho could depend on localized PtdIns(3,4,5)P 3 enrichment.…”
Section: Contractile Actomyosin Networkmentioning
confidence: 99%